'Her haggling nature never leaves her'. Dutch identity and Jewish stereotypes in the writings of Nicolaas François Hoefnagel (1735–1784). Issue 3 (2nd September 2017) - Rädecker, Tsila
Abstract: This article investigates how Nicolaas François Hoefnagel (1735–1784) uses pejorative images of the Jew to delineate the boundaries of Dutch identity. It explores Hoefnagel's dislike for Jews and his quest to morally enhance the Dutch. Against the background of contemporary situations, Hoefnagel set old stereotypical images of the Jew. The Jew became in this respect an instrument for the moral rearmament of the Dutch nation. As such this article will show that his construction of Jewish stereotypes served as a sounding board for Dutch identity.